ANALISA PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus pada Perusahaan Manufaktur di Bandung - Setya Nusa, Inta Budi; S, Sianita Devi (JEMBA, 2023)
This research aims to assess the extent of impact that internal control and the competence of human resources have on the quality of financial statements within manufacturing company in Bandung. The research employs both descriptive and quantitative methods. The study's population comprises personnel within manufacturing company in Bandung, and purposive sampling is employed as the sampling technique. Data analysis involves multiple SEM PLS analysis, tested using SPSS 23.0 for Windows software and SMART PLS. The findings of hypothesis testing in this research reveal that (1) internal control significantly influences the quality of financial statements, and (2) human resource competence also significantly influences the quality of financial statements at